European Union preferential trade agreements with developing countries and their impact on Colombian and Kenyan carnation exports to the United Kingdom - Muhammad, Andrew; Ngeleza, Guyslain K. (International Food Policy Research Institute, 2009)
United Kingdom (UK) demand for carnations by exporting country was estimated using a production version of the Rotterdam model, and model estimates were used to assess the effects of EU preferential trade agreements on import demand. Of particular importance was how these agreements affected Colombian and Kenyan carnation exports to the UK, the second largest market for Colombian carnations and the largest market for Kenyan carnations. Results showed that Colombia benefited from preferential access to the UK more so than Kenya: the benefit to Colombia was due to both trade creation and diversion, whereas the benefit to Kenya was mostly due to trade diversion. Results further showed that the competition between Colombian and Kenyan carnations was insignificant, and there was no evidence that the preferences given to Colombia harmed Kenya or vice versa.